On Integrability of a Special Class of Two-Component (2+1)-Dimensional Hydrodynamic-Type Systems - Pavlov, M.V.; Popowicz, Z. (Symmetry, Integrability and Geometry: Methods and Applications, 2009)
The particular case of the integrable two component (2+1)-dimensional hydrodynamical type systems, which generalises the so-called Hamiltonian subcase, is considered. The associated system in involution is integrated in a parametric form. A dispersionless Lax formulation is found.